Laundry Drying Chambers with Greenhouse Effect (GHE) Utilization - Lukman Hadiwijaya; Muhammad Furqon; Abdul Hamid; Agustia Dwi Kurniasih; Amin Jakfar; Mohammad Anas Fikri (Techno Bahari, 2025)
The greenhouse effect is defined as an increase in the earth's temperature. The increase in the earth's temperature is caused by the trapping of long-wave (infrared) sunlight by greenhouse gases. The greenhouse effect (GHG) is in the troposphere, which is the atmospheric layer on the earth's surface. The purpose of making a dryer by utilizing the greenhouse effect as a medium to help overcome the problem of drying clothes that have been relying on solar heat. But it is different when the rainy season arrives, by utilizing solar heat energy and managing it in such a way by using the greenhouse effect system (Green House Effect). In this research, we found that equipment with a base material made of glass can absorb heat faster, because the glass material has a fairly high thermal conductivity value. By applying heat transfer study materials, so that the trapped heat can be used as one of the sources of disposable dryers. Providing an exhaust fan on the roof of the tool as a mass transfer medium for evaporation of water in the dryer. The size of the tool to be made is 200 x 180 x 60 cm using a frame and galvanized glass. The efficiency obtained from the dryer is 8.98% in cloudy and 8.94% in sunny weather.